C‐myc in Kaposi's sarcoma: analyses by fluorescent in situ hybridization and immunohistochemistry. (7th August 2012) - Feller, K.; Yang, S.; Tung, N.; Lee, J.; Mahalingam, M.
Abstract Background The c‐myc proto‐oncogene plays a central role in the regulation of cellular transcription, differentiation, and apoptosis, and has been shown to be deregulated in many types of human cancer. Recent findings have demonstrated its amplification in select vascular neoplasms, such as secondary angiosarcomas, suggesting a role in angiogenesis as well. In vitro studies have shown that the c‐Myc protein is an important regulatory molecule of spindle cell proliferation and migration in Kaposi's sarcoma (KS). Objectives In light of these findings, our primary aim was to ascertain whether c‐myc, by promoting proliferation and angiogenesis, is an essential co‐factor in the aetiopathogenesis of KS. We also attempted to determine a correlation between immunohistochemical expression of the c‐Myc protein and c‐myc gene copy amplification using fluorescent in situ hybridization (FISH). Methods Samples analyzed included archival tissue of KS (n = 24). PCR for detection of Kaposi's sarcoma‐associated herpesvirus DNA was performed on all samples of KS. For FISH analyses, a dual‐labelled technique was employed and probes for the c‐myc gene and chromosome 8 were used. The monoclonal anti‐c‐myc antibody, 9E10, was used for immunohistochemical analyses. Results While FISH analyses revealed no amplification of c‐myc in any of the cases of KS, immunohistochemical analyses revealed positive staining for c‐Myc in 13/24 cases (54%). Conclusions Amplification of the c‐myc gene was not witnessed in this preliminary study of 24 cases and thus cannot be correlated with the expression of the c‐Myc protein.